Integrating Character Education into Maritime Vocational Learning: Evidence from Indonesian Vocational Schools - Wegig Pratama (Universitas Sultan Ageng Tirtayasa, 2026)
This study aims to analyze the integration of character education in maritime vocational learning within Indonesian vocational high schools. A qualitative approach employing a case study design was used to explore how character values are internalized within practice based learning environments. Data were collected through observations, semi-structured interviews, and document analysis involving teachers and students in maritime vocational programs. The data were analyzed using thematic analysis to identify recurring patterns of character integration. The findings indicate that character education is implicitly embedded in practical learning activities, resulting in the development of eight key character values: discipline, responsibility, teamwork, safety awareness, integrity, work ethic, independence, and leadership. These values are cultivated simultaneously through structured, procedural, and experiential learning processes that closely mirror real-world working conditions. The results demonstrate that practice-based learning not only enhances technical competencies but also functions as an effective medium for fostering professional character. This study contributes to the literature by offering a process oriented and context-specific understanding of character integration in maritime vocational education. The findings suggest that vocational learning should explicitly incorporate character indicators within practical activities to ensure alignment between educational outcomes and industry demands. Furthermore, this study provides practical insights for educators and curriculum developers in designing more holistic vocational training models that integrate both technical and character development.